Pemanfaatan Zakat Produktif sebagai Penggerak Ekonomi Inklusif (Studi pada Usaha Mikro Penerima Bantuan Zakat Produktif Lazisnu di Desa Wedoro) - Huda, Bakhrul; Jimly Hasanal Adhim, Abdullah (Institut Agama Islam YPBWI Surabaya, 2024)
This research discusses the utilization of productive zakat distributed by Lazisnu and its impact on inclusive economic mobilization in Wedoro Village. Productive zakat is used by Lazisnu as business capital for micro business actors with the aim of increasing production capacity and musta?iq welfare. This research uses a qualitative approach through data collection by interview, observation, and documentation. The results showed that 80% of zakat recipients experienced an increase in business turnover of 30-50% in six months, which contributed to an increase in living standards for 70% of productive zakat recipients. However, challenges in business financial management became an obstacle faced by some recipients. This study concludes that productive zakat has a significant role in promoting inclusive economy, but its sustainability requires support in the form of intensive mentoring and training for beneficiaries.